FurtunateMatcher: An AI-powered pet adoption counseling system utilizing NLP, collaborative filtering, and content-based filtering algorithm for optimal pet-adopter matches - Baguinaid, Jasmine A; Eugenio, Jannah Mae M.; Jabal, Maria Lourdes S.; Paderes, Marian B. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2